Stress distribution in endodontically treated and differently restored teeth with periapical lesions: a 3D FEA study - Ömer Kırmalı; M. Barış Akar; H. Kürşat Çelik; Kürşat Er (BMC Oral Health)
Abstract Background The mechanical performance of post materials used in endodontically treated teeth under occlusal loading is a critical determinant of long-term restorative success but remains insufficiently understood. In this study, stress distributions within teeth with periapical lesions restored using different post materials, as well as their surrounding tissues under occlusal load, were investigated using advanced engineering simulation technique. Materials and methods The finite element method based engineering analysis technique was employed, and five incisor tooth models representing healthy teeth and teeth restored with different post materials were used: (Model 1) healthy tooth; (Model 2) tooth with root canal treatment (RCT), periapical lesion, and metal-supported porcelain crown; (Model 3) tooth with a periapical lesion, fibre post, and metal-supported porcelain crown; (Model 4) tooth with a periapical lesion, cast metal post, and metal-supported porcelain crown; and (Model 5) tooth with a periapical lesion, zirconia post, and metal-supported porcelain crown. A static load of 100 N was applied to the palatal surface at an angle of 135° to the longitudinal axis. Equivalent stress distribution was analysed using the von Mises criterion, with particular attention to stress magnitudes within the tooth structure, post material, surrounding bone, and periapical region. Results Models 1, 2, and 3 exhibited stress concentrations primarily in the cervical and middle thirds of the root, with the highest stresses localised in the cervical region. The healthy model (Model 1) demonstrated the highest maximum equivalent stress (80.687 MPa), followed by Model 3 (76.681 MPa) and Model 2 (54.188 MPa). The presence of periapical lesions reduced overall stress levels due to the localised softening of the trabecular bone. Models 4 and 5 showed higher stress concentrations within the post materials (70.49 MPa and 69.27 MPa, respectively). In all models with lesions, stress within the lesion area remained consistently low (0.0164–0.0191 MPa). Conclusions Fibre-reinforced posts demonstrate superior biomechanical performance in endodontically treated teeth with periapical lesions, providing a stress distribution pattern that more closely resembles that of healthy teeth compared to rigid post materials.